ÐžÑÐ¾Ð±ÐµÐ½Ð½Ð¾ÑÑ‚Ð¸ Ñ€Ð°Ð·Ð²Ð¸Ñ‚Ð¸Ñ Ð½ÐµÐºÑ€Ð¾Ð·Ð° Ð¼Ð¸Ð¾ÐºÐ°Ñ€Ð´Ð° Ð¸ Ñ€ÐµÐ¼Ð¾Ð´ÐµÐ»Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ ÑÐµÑ€Ð´Ñ†Ð° Ð¿Ð¾ÑÐ»Ðµ Ð¿ÐµÑ€ÐµÐ²ÑÐ·ÐºÐ¸ ÐºÐ¾Ñ€Ð¾Ð½Ð°Ñ€Ð½Ð¾Ð¹ Ð°Ñ€Ñ‚ÐµÑ€Ð¸Ð¸ Ð¸ Ð»Ð¾ÐºÐ°Ð»ÑŒÐ½Ð¾Ð¹ ÐºÑ€Ð¸Ð¾Ð´ÐµÑÑ‚Ñ€ÑƒÐºÑ†Ð¸Ð¸ Ð»ÐµÐ²Ð¾Ð³Ð¾ Ð¶ÐµÐ»ÑƒÐ´Ð¾Ñ‡ÐºÐ° - Chizh, N. A.; Babayeva, A. G.; Sleta, I. V.; Galchenko, S. E.; Sandomirsky, B. P. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2024)
There were studied the destructive and reparative processes after myocardium injury, induced by left coronary artery ligation and local cryodestruction of left ventricle. The dependency of myocardium injury depth on cryoinjury duration was shown. After coronary artery ligation the left ventricle wall was damaged over the entire thickness. The most pronounced differences in microvasculature state in central and boundary areas of myocardium injury after both coronary artery ligation and local cryodestruction were revealed to the 14th day. The recovery of microvasculature indices in cardiac peripheral areas was noted in earlier terms after left coronary artery ligation if compared to the cryoinjury. Histological studies of the heart tissue revealed in the area of injured myocardium the development of inflammatory response, alternated with fibrosis process with connective tissue scar formation. Application of cryosurgical method for heart injury resulted in formation of the connective tissue scar in earlier terms.